Analysis of Relationship Between Conversational Media Applications and Social Media with Social Capital in Disaster Mitigation at the area of Bogor Regency, Indonesia - Irwan, Irwan; Zusmelia, Zusmelia; Siska, Felia; Mazya, Thita M; Elvawati, Elvawati; Siahaan, Kevin William Andri (Future Science / FSH-PH Publications, 2022)
The study analyzes the relationship between conversational applications (WhatsApp) and social media (Facebook and Instagram) through social capital in disaster mitigation at the Ciliwung Riverbank, Tugu Utara Village. This study used Mayfield's social media theory and Lasser's social capital theory in analyzing disaster mitigation. This study used a post-positivistic paradigm and combined two qualitative and quantitative approaches. Data collection techniques were carried out by direct observation, in-depth interviews, document studies, and distributing questionnaires through survey techniques. Qualitative data analysis used the Miles and Huberman model and quantitatively used descriptive statistics with correlation analysis. The results showed that the relationship between conversational media applications and social media with social capital was highly correlated and obtained a value above 0.75. This showed a very strong relationship before, during, and after the disaster. Users of conversational media applications and social media build social capital to help each other, build social networks and social relations, trust and cooperation to achieve common goals. The power of social capital through the application of conversational media and social media forms social interaction and social communication based on technology or digital in disaster areas.